Internalization of Religious Moderation Based on Religious Education - Lesmana, Erik Alga; Leksono, Aris Adi; Ismawati (Perkumpulan Dosen Tarbiyah Islam Indonesia, 2024)
The study employs a qualitative research methodology utilizing a case study framework, conducted at SMPN 89 Jakarta. Methods for data collection encompass observation, interviews, and documentation, drawing from schoolteachers and students as primary sources. Analysis methods include data collection, reduction, presentation, and deduction, with source triangulation used to validate the data. Efforts are directed towards curbing intolerance and extremism through the promotion of religious moderation. A strategy devised by school principals and teachers, known as the '5 M' approach (smiles, greetings, manners), is implemented to instill moderate religious values among the school community. Regular teacher coaching sessions are conducted to foster a culture of diversity, perceived as the divine will. The religious environment at SMPN 89 Jakarta exhibits moderate religiosity and embraces diversity, although religious teachers tend to prioritize traditional identity beliefs during the implementation of religious supervision and understanding.